Use of electric arc furnace slag for producing concrete paving blocks - Penteado, Carmenlucia Santos Giordano; Evangelista, Beatriz Leão; Ferreira, Gisleiva Cristina dos Santos; Borges, Pedro Henrique Andrade; Lintz, Rosa Cristina Cecche (Ambiente Construído, 2019)
In this study the electric arc furnace slag was used as coarse natural aggregate substitute in concrete paving blocks production. The concrete mixture was defined by using weight proportions in the ratio of 1:2:3:0.51 (cement:sand:coarse aggregate:water) in order to obtain a compressive strength of 35 MPa. Four groups of concrete were prepared: a reference recipe and three others with the slag replacing the natural aggregate in the proportions of 25%, 50% and 75%. The compressive strength was not influenced by the slag content; however, it was influenced by the curing age, as the sample with 75% of slag addition had its compressive strength increased by 13.5% from 7 to 56 days. Water absorption presented a slightly reduction with slag addition. The results of compressive strength and water absorption met the Brazilian technical requirements, making the paving blocks suitable for use in light vehicle traffic. The results obtained in this study highlight the influence of the production process in the final quality of the steel slag, and the need of stablishing technical and environmental requirements to guide and promote the safe use of electric arc furnace slag in concrete.